A Study of Ethical Considerations in Supply Chain Management Research and Practice - Harding, Fiona (2009)
This report investigates how ethical factors are being considered in supply chain management research and practice. A literature review defines the key terms and identifies several gaps in research, two of which are addressed in this paper; firstly how firms currently evaluate the ethical performance of their suppliers and secondly how existing supply chain management theory should be amended to incorporate ethical considerations.